O designer e a prática profissional na indústria automobilística no Brasil - Pizarro, Carolina Vaitiekunas [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Among the objects produced on an industry scale, the car is an emblematic and a complex product that is result of years of research, which contributed to the improvement of its various components and guided its evolution along the time. Especially after the industrial Revolution, the progress, made in terms of project practice, speed of production and the increasing market competition, outlined the formation of the industrial designer, which over time also became responsible for vehicles projects in the automotive industry of nowadays, is incubent on designers to design and monitor the development of vehicles taking into account both the objective aspects such as safety, comfort and performance, like the subjective ones - potential to evoke emotions and identification with the user - at the production. The present research aimed to investigate how the designers of companies in the automotive sector in Brazil perceive the processes involved in their work routine, raising aspects of the practice which influence the performance of these professionals and the process of car design. It sought at the same time, contribute to the production and dissemination of scientific knowledge in this area of design research which is still timidly studied in Brazil. To this end, we resorted to the qualitative/quantitative research approach, initially applying open interviews with experts, from which were obtained the necessary parameters to the elaboration of the closed questionnaires subsequently applied to a sample group studied in order more accurate data to the research topic. The results elucidate various aspects related to professional practice and its analysis allowed to make interferences about the activity of the brazilian automobile designer, building a current overview of the profession from the look the professionals designer, building a current overview of the profession from the look of the professionals themselves. Finally, the research results...

Entre os objetos de uso produzidos em escala industrial, o automóvel figura como um emblemático e complexo produto resultante de anos de pesquisas, as quais contribuíram para o aprimoramento de seus diversos componentes e pautaram sua evolução. Notadamente após a Revolução Industrial, os avanços obtidos em termos de prática de projeto, velocidade de produção e concorrência crescente de mercado, delinearam a formação da atividade do desenhista industrial ou designer, o qual, ao longo do tempo, tornou-se responsável também pelo projeto de veículos. Na indústria automotiva da atualidade, é incubência dos designers projetar e acompanhar o desenvolvimento de automóveis, levando em consideração tanto aspectos objetivos como segurança, conforto e desempenho, quanto subjetivos - potencial para evocar emoções e identificação com o usuário - na produção do produto. A presente pesquisa se propôs a investigar como os designers de empresas do setor automobilístico no Brasil percebem os processos envolvidos em sua rotina profissional, levantando aspectos da prática que influenciam no desempenho desses profissionais e no processo de designer de automóveis. Também objetivou contribuir para a produção e divulgação dos conhecimentos científicos nesta área do design que é qualitativo/quantitativo realizando em um primeiro momento entrevistas abertas com especialistas, a partir das quais se obtiveram os parâmetros necessários à elaboração de questionários fechados posteriormente aplicados a uma amostro do universo pequisado, visando à obtenção de dados mais precisos em relação ao tema pesquisado. Os resultados elucidaram variados aspectos referentes à prática profissional e a análise destes permitiu a realização de inferências sobre a atividade do designer de automóveis brasileiro, construindo um panorama atual da profissão a partir do olhar dos próprios profissionais. Por fim, os resultados da...
Keywords: Desenho industrial; Automoveis; Indústria automobilística - Brasil; Industrial design